Investigating and examining the structure and the difficulties of tertiary learners in essay writing: Rhetorically-based approach - Sitorus, Nurhayati; Siregar, Eva Fitri Y.; Siagian, Beslina Afriani; Lestari, Febrika Dwi; Silitonga, Harpen (Linguistics and Culture Review, 2021)
Rhetorical approach is a tool that can be used to analyze essay writing. Not only to analyze but also to help us making an essay. By using rhetorical, the writer can narrate, describe, classify, and give example. This research discusses about the structure and the difficulties of tertiary learners in essay writing based on rhetorical approach. The sample of this research was tertiary learners and they became the source of the data in the research. Writing test was used as the instrument in the research. Here, the researcher asked the tertiary learners to write an essay. Then, analyzing the data based on rhetorically approach. The result of the study showed that 55,56% tertiary learners are able in writing an essay based on the rhetorically approach. And Based on the analysis, the researcher found tertiary learners’ difficulties in essay writing, namely grammar, vocabulary, cohesion and coherence, misspelling, developing and organizing idea, and arranging or building sentences are still based on first language.